IMPROVING THE COMMUNITY'S ABILITY TO ASSESS CHILDREN'S GROWTH AND FULFILLMENT OF FAMILY NUTRITION - Dian Isti Angraini (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Monitoring the growth and development of children in the first 1,000 days of life is very important given the rapid growth and development at this age. This very rapid brain development at the age of under 2 years (a critical period of development) is the right time to make recovery, if there are growth disorders and nutritional deficiencies. Increasing the community's ability to assess children's growth and development and fulfillment of family nutrition is very important as an effort to optimize the process of child growth and development as the nation's next generation. The purpose of this programme is to improve the ability of the community (independently) in assessing children's growth and development and fulfilling family nutrition. The methods used in this programme are focus group discussions as the basis for making modules, health promotion with interactive lectures and discussion techniques, and simulations of how to assess toddler growth and development using maternal and child health books (KIA) and family nutrition fulfillment. This programme was carried out for 1 day and took place in Kaliasin Village, Tanjung Bintang District, South Lampung Regency. The participants were 30 people who were members of the community in Kaliasin Village, Tanjung Bintang District, South Lampung Regency. The results of the evaluation found that there was an increase in participants' understanding as much as 90% became a good understanding, 10% of participants had a fairly good understanding, and none of the participants had a poor understanding of how to assess the growth and development of toddlers and the fulfillment of family nutrition. The average pretest result was 50.5 and an increase in the posttest result was 83.5. Based on the analysis using the Wilcoxon test, it was found that there was a statistically significant mean difference between the pretest and posttest scores participants on how to assess toddler growth and family nutrition (p=0.000). Increasing the community's ability to assess children's growth and development and fulfillment of family nutrition with this technique of increasing knowledge and skills has proven to be effective.